Chaos and creativity from a methodological vocabulary in the embodied learning of the research seedbed - Calderón-Urriola, Nicolás Fidel (2023)
The objective of the study was to describe chaos and creativity from a methodological vocabulary in the embodied learning of the research seedbed. From January to December 2022, a pilot project called "Formándose y Formando" was carried out with four research seedlings of the Universidad Nacional ¨San Luis Gonzaga¨, Ica, Peru. Four pedagogical dimensions were established to describe conceptualization criteria in three stages and then the embodied learning of the methodological vocabulary was considered with five structures in a pedagogical model: title, introduction, objectives, measurement and proposal improvement. Conceptualization criteria were recognized for two levels: practical and theoretical of the methodological vocabulary. The bigraphy yielded as percentage of variance the title (46.15%), introduction (23.22%), objectives (20.18%), methods (9.64%) and proposal improvement (0.81%). It was concluded, that the description of the chaos and creativity of the methodological vocabulary in the embodied learning of the research seedbed through the pedagogical model defined the embodiment of a cognition and learning where the knowledge integration skills were measured with conceptualization criteria.